1980
DOI: 10.1021/bi00545a030
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of the individual steps in the reaction of lysozyme with the trimer and hexamer of N-acetyl-D-glucosamine at subzero temperatures

Abstract: The reaction of hen egg white lysozyme with chitotriose and chitohexose has been investigated at temperatures to below -100 degrees C by using aqueous methanol and dimethyl sulfoxide cryosolvents. Initial investigations involving the effects of increasing cosolvent concentration on the catalytic and structural properties of the enzyme indicated that both methanol and dimethyl sulfoxide cryosolvents, at subzero temperatures, had no adverse effects on lysozyme. Time-dependent changes in the fluorescence emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Previous studies (Smith-Gill et al, 1982) have already shown that the dye Biebrich Scarlet [known to bind exclusively to the F site of HEWL (Holler et al, 1975)] is displaced by HyHEL-5 from HEWL, indicating that the dye itself lies at least partially in the region of residues 45-47. In Figure 1, the results of competition experiments are shown in which different oligosaccharides of GlcNAc are allowed to compete with HyHEL-5 in binding to HEWL. These experiments were conducted at -20 °C, at which temperature no catalysis occurs but binding is actually stronger (Douzou et al, 1974;Fink et al, 1980).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies (Smith-Gill et al, 1982) have already shown that the dye Biebrich Scarlet [known to bind exclusively to the F site of HEWL (Holler et al, 1975)] is displaced by HyHEL-5 from HEWL, indicating that the dye itself lies at least partially in the region of residues 45-47. In Figure 1, the results of competition experiments are shown in which different oligosaccharides of GlcNAc are allowed to compete with HyHEL-5 in binding to HEWL. These experiments were conducted at -20 °C, at which temperature no catalysis occurs but binding is actually stronger (Douzou et al, 1974;Fink et al, 1980).…”
Section: Resultsmentioning
confidence: 99%
“…Substrate inhibition of antibody binding to HEWL was examined in a low-temperature ELISA plate-binding assay. It is known from previous work (Douzou et al, 1974;Fink et al, 1980) that, at temperatures below -20 °C in a variety of antifreeze buffers, the rate of lysozyme-catalyzed hydrolysis approaches zero (i.e., kcat = 0) for cell wall substrates and for (GlcNAc)6. However, the binding of substrates to the enzyme is actually enhanced (Douzou et al, 1974;Fink et al, 1980).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). Considerable efforts have previously been made, with HEWL, to ®nd such a condition yet in no case have these efforts proven successful 9,10 . This observation strongly suggests that, for HEWL, hydrolysis of the intermediate (k 3 ) occurs at a much greater rate than does its formation (k 2 ).…”
mentioning
confidence: 99%